Exploring Emerging Technologies in Geotechnical Engineering : A Critical Literature Review - Muhammad Ade Kurnia Harahap; Ramdan Yusuf; Aat Ruchiat Nugraha; Arya Ningsih (Indonesia Journal of Engineering and Education Technology (IJEET), 2024)
Geotechnical engineering plays an important role in the development of safe and sustainable infrastructure. New technological developments continue to open up opportunities to improve geotechnical practices and answer increasingly complex challenges. This research aims to Research and analyze new emerging technologies in geotechnical engineering, as well as evaluate their potential to improve geotechnical practices and solutions. This research uses a comprehensive literature review and critical analysis of scientific literature, industry publications, and case studies related to new geotechnical technologies. The results of this study conclude that new emerging technologies in geotechnical engineering have great potential to improve geotechnical practices and solutions. The application of these technologies can help improve the efficiency, safety, and sustainability of geotechnical projects